El efecto de arroyos tributarios de menor orden sobre el perifiton de un río de llanura - Gari, N. (2006)
Confluence zones are important places to analyze discontinuities that succeed in the river continuum, when two streams of different order link up with their collector. In this work we analyzed the periphyton composition and structure in the confluence of two mountain streams, where Chocancharava river (Cuarto river) foothill reach begins, in Córdoba province. Monthly periphyton samples were taken by scraping a known surface, in three sites located in Piedras Blancas and San Bartolomé stream confluence at 550 m a.s.l. TWINSPAN classification and sample and species ordinations by means of Canonic Correspondence Analysis (CCA) were carried out. Seventy one algae species were determined. Bacillarophyceae and Chlorophyceae presented higher species richness. Dominant species were Cocconeis placentula var. euplypta and Achnanthidium minutissimum, both exhibited an annual bimodal distribution pattern, with maximal densities in autumn and spring. CCA clusters demonstrated seasonal changes in periphyton structure. Summer species were associated to higher temperature and precipitations, and winter species (were associated) to higher conductivity and pH. The tributary of minor order, San Bartolomé stream, evidenced a wider distance in the sample grouping; its flora was different in winter months, during the phase of low water levels. From the obtained results it is concluded that at the confluence sectors the composition and structure of the higher order stream is continuous with the principal river during low water levels while, during high water levels, the periphyton of both tributaries colonize the receiving river.